(untitled) (Global Journal of Management and Business Research, 2015)
Since the Silk Road Economic Belt is proposed, many areas, countries and provinces have established the development strategy, to strengthen regional exchanges and cooperation. The Silk Road Economic Belt city forum held in the big city of China and the five Central Asian countries. Most of these regions have layout around the warehousing and transportation, commerce & trade logistics, regional finance, tourism and cultural exchange industry. The vanguard and hub strategy in Shaanxi province; golden section in Gansu province and major scenic spots of Xinjiang strategic fulcrum of positioning strategy. The emergence of the industrial layout duplication is inevitable due to lack of communication, positioning and lack of overall strategy.